Secukinumab shows sustained efficacy and low structural progression in ankylosing spondylitis: 4-year results from the MEASURE 1 study. (19th December 2018) - Braun, Jürgen; Baraliakos, Xenofon; Deodhar, Atul; Poddubnyy, Denis; Emery, Paul; Delicha, Eumorphia M; Talloczy, Zsolt; Porter, Brian
Abstract: Objective: To evaluate the effect of secukinumab, a fully human anti-interleukin-17A monoclonal antibody, on efficacy, imaging outcomes, and safety through 4 years (208 weeks) in patients with ankylosing spondylitis. Methods: Patients opting to enrol had completed 2 years' treatment in the MEASURE 1 core study with subcutaneous secukinumab 150 or 75 mg every 4 weeks (q4Wk), following intravenous loading to Week (Wk) 4, or placebo treatment to Wk16/24. Up-titration from secukinumab 75–150 mg q4Wk was permitted following a protocol amendment. Efficacy is reported for patients originally randomized to secukinumab. Radiographic changes were assessed using the modified Stoke Ankylosing Spondylitis Spinal Score (mSASSS) and changes in MRI measures of inflammation using the Berlin scoring method. Safety and tolerability were evaluated. Results: Among 274 extension study participants, 89.7% (78/87) and 93.0% (93/100) originally randomized to secukinumab 150 and 75 mg, respectively, completed 208Wk. Through Wk208, Assessment of Spondyloarthritis International Society 20/40 (observed) were 79.7%/60.8% (150 mg), 71.0%/43.5% (75 mg) and 80.0%/76% (up-titrators; n = 25). Mean (s.d.) changes in mSASSS were 1.2 (3.91) (150 mg), 1.8 (4.32) (75 mg) and 1.6 (5.67) (up-titrators). No radiographic progression (mSASSS change from Baseline < 2) was observed in 79% of patients receiving either secukinumab dose. Exposure-adjusted incidence rates per 100 patient-years were: serious infections (1.0), Candida infections (0.4), Crohn's disease (0.6), ulcerative colitis (0.2), and malignant/unspecified tumours (0.5), with no new safety signals. Conclusion: Through 4 years, secukinumab provided sustained efficacy on signs and symptoms, and MRI outcomes, a low rate of radiographic progression and a consistent safety profile. Trial registration: NCT01863732.